O princípio da publicidade no direito processual penal - Cabrera, Fernando José Bellini (2005)
The work methodology consists of the initial study of the legal system, using a general theory of law approach, and considering that the scientific knowledge of law itself is essentially a study of logical causes, which are the general principles originated in positive law. Thus, the rules of positive law are merely logical consequences of general principles. Furthermore, this initial study on legal order, confirms that to deny that such order is based on justice and on the requirements of human nature, would be equivalent to reducing law to a simple product of the dominant power of the social environment, whether it is the desire of a chief, a legislative or judging entity to which coercive powers have been granted, or even the opinion of the majority. Principles are the nuclear commandments of a system and, therefore, this paper, making notorious use of the approach of the principle of advertising in criminal procedural law, targets the study of its repercussions in the criminal procedure, in the light of the Federal Constitution of 1988, and is also based on the fundamental guarantees of human beings, such as the principle of dignity and the Democratic State of Law